Protein-protein interaction networks reveal therapeutic targets in Khlu, Hoary basil and Indian mulberry for inflammation, diabetes and diarrhea - Sootanan, Pitak; Sornsiri, Jidapa (Agriculture and Natural Resources, 2024)
Importance of the work: Khlu, Hoary basil and Indian mulberry leaves have important medicinal properties for treating inflammation, diabetes and diarrhea. Objectives: To elucidate the roles and molecular mechanisms of Khlu, Hoary basil and Indian mulberry leaf contents based on protein-protein interaction network analysis. Materials & Methods: Protein-protein interaction networks were constructed for Khlu, Hoary basil and Indian mulberry leaves using databases (ChEMBL, STITCH, STRING and DisGeNET). The developed networks, exhibiting scale-free, small-world and modular characteristics, were analyzed to identify and interpret disease-related modules for inflammation, diabetes and diarrhea. Results: Leaves from Khlu, Hoary basil and Indian mulberry influenced biological processes linked to inflammatory mediators, insulin resistance and colon fluid secretion, suggesting potential mechanisms to prevent inflammation, diabetes and diarrhea. Active ingredients from these leaves formed interaction networks with characteristics conducive to module analysis, identifying target protein modules for these diseases. Common biological processes —lipid metabolism, metal ion transport and adenosine metabolism —impacted insulin resistance, glucose regulation and inflammatory mediator production. Main finding: Plausible mechanisms supporting their effectiveness were development for Khlu, Hoary basil and Indian mulberry leaves that are traditionally used by local people for treating inflammation, diabetes and diarrhea. Protein-protein interaction network analysis revealed their influence on inflammatory mediators, insulin resistance and glucose regulation. The identified protein groups could be valuable targets for future research on their medicinal properties.